(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
This research investigates the relationship between leadership styles and employee work engagement, with the aim of identifying the most effective leadership styles in increasing work engagement. Using approach Systematic Literature Review (SLR), this research analyzes various studies related to transformational, transactional, autocratic and participative leadership styles. The research results show that transformational and participative leadership styles significantly increase employee work engagement, while autocratic and transactional styles tend to reduce engagement. The implications of this research provide practical recommendations for organizations to adopt a leadership style that supports employee empowerment and intrinsic motivation.